Comparison of Applications of Various Organic and Inorganic Fertilizers on the Growth and Yield of Cayenne Pepper - I Gusti Nyoman Arthanawa; I Ketut Darmawan; Dewa Putu Semara Yana; Yohanes Parlindungan Situmeang; I Dewa Nyoman Sudita; I Nyoman Astika (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
Cayenne pepper is one of the agricultural commodities that has high economic value and its demand continues to increase along with the development of the population. Efforts to increase the production and quality of various types of plants continue to be carried out, by utilizing various types of fertilizers. The purpose of this study was to determine the response of growth and yield of cayenne pepper using organic and inorganic fertilizers. This research was carried out at the Experimental Garden of the Local Waste Processing Site in Kusamba Village, Klungkung Regency, and the Laboratory of the Agrotechnology Study Program, Faculty of Agriculture, Warmadewa University, Denpasar from March to November 2021. The method used in this study was experimental, using a Randomized Block Design (RBD). ) with 1 factor and 4 replications. The variables observed were plant height, number of leaves, stem diameter, number of fruit, fruit weight per plant, and fruit weight per ha. The results showed that the application of various types of fertilizers can increase all observed variables. The best fertilizer for the growth and yield of cayenne pepper is NPK fertilizer.